2020
DOI: 10.1002/bab.1853
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the current status and advancement of diabetes mellitus type 2 and to avert complications: An overview

Abstract: Type 2 diabetes mellitus (T2DM) is an endocrine metabolic disorder, occurring worldwide due to aging, advancement in lifestyle by modernization. T2DM is characterized by higher levels of glucose in the blood due to unresponsive secretion of pancreatic insulin and insulin activity or altogether. T2DM is regarded as a powerful genetic susceptible disease that leads to high risk with insulin resistance and β‐cell dysfunction. To manage and overcome type 2 diabetes, physical activity, diet strategies, and other th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 89 publications
0
20
0
Order By: Relevance
“…Type 2 diabetes mellitus (T2D) comprises 90% of patients with diabetes and is caused by a combination of genetic and lifestyle factors, including insulin resistance, excess body weight and physical inactivity [ 1 , 2 ]. Currently, there are about 463 million of T2D patients worldwide and the disease causes 4.2 million of deaths annually.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2D) comprises 90% of patients with diabetes and is caused by a combination of genetic and lifestyle factors, including insulin resistance, excess body weight and physical inactivity [ 1 , 2 ]. Currently, there are about 463 million of T2D patients worldwide and the disease causes 4.2 million of deaths annually.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes (T2D) is a complex disease caused by polygenic inheritance and environmental interactions, which characterized by chronic low-grade inflammation and hyperglycemia [ 10 13 ]. It is well known that insulin resistance and islet beta cell dysfunction are the pathophysiological mechanisms of T2D [ 14 , 15 ]. Recent studies showed that serum ADA levels and its isoenzymes are significantly higher in patients with T2D than in healthy controls [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…DM affects millions of people and its prevalence is increasing day-by-day [2]. In developed countries, it is projected that about 87% to 91% of registered diabetic individuals have T2DM, 7% to 12% have T1DM, while 1% to 3% have other forms of DM [3,4]. New statistics from IDF 2019 reveal that approximately 463 million adults were living with diabetes by 2045 this will rise to 700 million.…”
Section: Introductionmentioning
confidence: 99%
“…In people of South Asian heritage, T2DM is up to six times more common, and the largest ethnic minority in the United Kingdom is people of South Asian (SA) ethnicity (of Indian, Pakistani and Bangladeshi descent) who in many metropolitan locations now constitute the dominant ethnic community [7]. The prevalence of diabetes in SA is 23 % which is very high compared to other ethnic groups in United Kingdom (UK) [4]. It has also been predicted that the South Asian subcontinent will be having the greatest burden of diabetes worldwide by 2030 [8,9].…”
Section: Introductionmentioning
confidence: 99%